Diagnosis and misdiagnosis of adult neuronal ceroid lipofuscinosis (Kufs disease) - Berkovic, Samuel F; Staropoli, John F; Carpenter, Stirling; Oliver, Karen L; Kmoch, Stanislav; Anderson, Glenn W; Damiano, John A; Hildebrand, Michael S; Sims, Katherine B; Cotman, Susan L; Bahlo, Melanie; Smith, Katherine R; et al. (Neurology, 2016)
OBJECTIVE: To critically re-evaluate cases diagnosed as adult neuronal ceroid lipofuscinosis (ANCL) in order to aid clinicopathologic diagnosis as a route to further gene discovery. METHODS: Through establishment of an international consortium we pooled 47 unsolved cases regarded by referring centers as ANCL. Clinical and neuropathologic experts within the Consortium established diagnostic criteria for ANCL based on the literature to assess each case. A panel of 3 neuropathologists independently reviewed source pathologic data. Cases were given a final clinicopathologic classification of definite ANCL, probable ANCL, possible ANCL, or not ANCL. RESULTS: Of the 47 cases, only 16 fulfilled the Consortium's criteria of ANCL (5 definite, 2 probable, 9 possible). Definitive alternate diagnoses were made in 10, including Huntington disease, early-onset Alzheimer disease, Niemann-Pick disease, neuroserpinopathy, prion disease, and neurodegeneration with brain iron accumulation. Six cases had features suggesting an alternate diagnosis, but no specific condition was identified; in 15, the data were inadequate for classification. Misinterpretation of normal lipofuscin as abnormal storage material was the commonest cause of misdiagnosis. CONCLUSIONS: Diagnosis of ANCL remains challenging; expert pathologic analysis and recent molecular genetic advances revealed misdiagnoses in >1/3 of cases. We now have a refined group of cases that will facilitate identification of new causative genes.
Keywords: Age of Onset; Neurons; neuronální ceroidlipofuscinózy; věk při počátku nemoci; Neuronal Ceroid-Lipofuscinoses; Diagnostic Errors; Young Adult; Lipofuscin; dospělí; Humans; chybná diagnóza; mladý dospělý; Adult; Adolescent; lipofuscin; neurony; lidé; mladiství